Front Cover: Isostructural Family of Rare‐Earth MOFs Synthesized from 1, 1, 2, 2‐Tetrakis(4‐phosphonophenyl)ethylene (Eur. J. Inorg. Chem. 34/2022). Issue 34 (10th November 2022) - Steinke, Felix; Otto, Tobias; Ito, Sho; Wöhlbrandt, Stephan; Stock, Norbert
Abstract : The Front Cover shows the diffraction of a focused beam on micro‐sized crystallites of Y‐CAU‐34 located on a carbon grid and the detection of the Rigaku HyPix‐ED detector, which is part of a dedicated electron diffractometer. The diffraction pattern was initially used to solve the crystal structure of Y‐CAU‐34, which was then used to determine the crystal structures of a series of porous metal phosphonates. The M‐CAU‐34 compounds were obtained from hydrothermal reactions employing the linker 1, 1, 2, 2‐tetrakis(4‐phosphonophenyl)ethylene and a series of rare earth nitrates. Only rare earth ions with an effective ionic radius of 92‐98 pm lead to the formation of CAU‐34. More information can be found in the Research Article by N. Stock and co‐workers .